2014
DOI: 10.1186/s13023-014-0214-5
|View full text |Cite
|
Sign up to set email alerts
|

Thymectomy for non-thymomatous myasthenia gravis: a propensity score matched study

Abstract: BackgroundThe efficacy of thymectomy in patients with non-thymomatous Myasthenia Gravis (MG) is still unclear. Main limitations have been variable outcome definitions, lack of a control group and adjustment for confounding.ObjectiveTo study the efficacy of thymectomy in achieving remission or minimal manifestation (R/MM) status in patients with non-thymomatous MG.MethodsPatients with generalized MG and minimum follow-up of 6 months were included. Demographic data and treatments were recorded, as well as the MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 26 publications
(24 reference statements)
0
19
0
2
Order By: Relevance
“…Several large retrospective data sets indicate that there is a significant increase in achieving minimal symptoms or remission in MG patients who had a thymectomy performed (2,3). Propensity matched data also supports these findings (4). These data sets are confounded by differences in surgical technique, lack of prospective randomization and limited follow up.…”
mentioning
confidence: 58%
“…Several large retrospective data sets indicate that there is a significant increase in achieving minimal symptoms or remission in MG patients who had a thymectomy performed (2,3). Propensity matched data also supports these findings (4). These data sets are confounded by differences in surgical technique, lack of prospective randomization and limited follow up.…”
mentioning
confidence: 58%
“…Незначительное ухуд-шение состояния больных с миастенией после опе-ративного вмешательства, не получавших в пред-и послеоперационных периодах плазмаферез, под-тверждает предположение некоторых авторов [8] о влиянии именно плазмафереза на состояние паци-ента в ближайшем послеоперационном периоде, не-жели непосредственно ТЭ как фактора, уменьшаю-щего клинические проявления миастении. Из паци-ентов, не вошедших в исследование, выделим 2 больных, которым в качестве предоперационной подготовки проводилась инфузия иммуноглобули-нов.…”
Section: Discussionunclassified
“…108 Another large retrospective study investigated the efficacy of thymectomy in nonthymomatous GMG and reported a 21% rate of remission or minimal manifestations in the thymectomy group at 5 years, compared with 6% in the control group. 109 The authors concluded that their study provides class III evidence of the efficacy of thymectomy in nonthymomatous MG. Longer duration of follow-up is associated with even higher rates of CSR, and has been reported to be as high as 72% at 10 years. 110 Despite these reports, the effectiveness of thymectomy is not universally embraced.…”
Section: Treatmentmentioning
confidence: 98%